The Deadly Duo of COVID-19 and Cancer! - Bora, Vivek R.; Patel, Bhoomika M. (Frontiers in Molecular Biosciences, 2021)
As of September 19, 2020, about 30 million people have been infected with the novel corona virus disease 2019 (COVID-19) globally, and the numbers are increasing at an alarming rate. The disease has a tremendous impact on every aspect of life, but one of the biggest, related to human health and medical sciences, is its effect on cancer. Nearly 2% of the total COVID-19 patients prior to May 2020 had cancer, and the statistics are quite frightening as the patient can be referred to as “doubly unfortunate” to suffer from cancer with the added misery of infection with COVID-19. Data regarding the present situation are scarce, so this review will focus on the deadly duo of COVID-19 and cancer. The focus is on molecular links between COVID-19 and cancer as inflammation, immunity, and the role of angiotensin converting enzyme 2 (ACE2). Complications may arise or severity may increase in cancer patients due to restrictions imposed by respective authorities as an effort to control COVID-19. The impact may vary from patient to patient and factors may include a delay in diagnosis, difficulty managing both cancer therapy and COVID-19 at same time, troubles in routine monitoring of cancer patients, and delays in urgent surgical procedures and patient care. The effect of anti-cancer agents on the condition of cancer patients suffering from COVID-19 and whether these anti-cancer agents can be repurposed for effective COVID-19 treatment are discussed. The review will be helpful in the management of deadly duo of COVID-19 and cancer.